Initiating Ṭibbun Nabawī in Local Agricultural Perspective Through Financing Products of Sharia Bank - Ahmad Mustofa (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
This study examines two areas in Islamic economics that have yet to be met in a productive partnership, namely (1) Islamic banking institutions and (2) economic activities in the agricultural sector. Islamic banking institutions limit contact with the agricultural sector because of the negative assumptions already attached to the gloomy prospects for agriculture. In contrast, the agricultural industry players have formal limitations in negotiating with banking institutions. From a local perspective, this research on 'Tibbun nabawi' seeks to open up opportunities for both parties in a productive and beneficial partnership. This is literature research, a qualitative approach utilizing the study of the living Quran. Utilization of the financing management pattern with a modified joint responsibility system is the most crucial result in this study so that partnerships between Islamic banking institutions and the agricultural industry can be realized immediately.